Introspection and Necessity1. (18th August 2016) - Stoljar, Daniel
Abstract: What is the connection between being in a conscious mental state and believing that you yourself are currently in that state? On the one hand, it is natural to think that this connection is, or involves, a necessary connection of some sort. On the other hand, it is hard to know what the nature of this necessary connection is. For there are plausible arguments according to which this connection is not metaphysically necessary, not rationally necessary, and not merely naturally necessary. If these arguments are correct, and if these options are exhaustive, while there is a necessary connection between a conscious state and the belief that you are in it, there is apparently no necessary connection it could be! This paper sets out this problem—the necessary connection problem, I will call it—and defends and explores a novel proposal about how to solve it.